Birds of Dang Deukhuri Foothill forests and West Rapti Wetlands: An Important Bird and Biodiversity Area, Nepal - Khanal, Chiranjeevi; Inskipp, Carol; Giri, Tikaram (Nepalese Journal of Zoology, 2024)
Information on the Dang Deukhuri Foothill Forests and West Rapti Wetlands Important Bird and Biodiversity Area (DDWR IBA) is updated. When the DDWR was first assessed as an IBA in 2005, little information about the area was available. IBA designation was based on the area supporting a significant population of one globally threatened species, white-rumped vulture Gyps bengalensis (A1). Although no bird survey had been carried out, the DDWR has a large area of suitable habitat thought very likely to support significant populations of bird species in the Indo-Malayan tropical dry zone, so fulfilling the biome-restricted species criterion (A3). Evidence for designation of the DDWR IBA was significantly strengthened in this study. A bird survey was carried out in the Deukhuri Valley in the DDWR IBA and a desk study researched other sources of bird records including ebird. A total of 319 bird species was recorded up to the end of April 2023 including significant populations of six globally threatened species (white-rumped vulture, slender-billed vulture Gyps tenuirostris, red-headed vulture Sarcogyps calvus, Egyptian Vulture Neophron percnopterus, steppe eagle Aquila nipalensis and great slaty woodpecker Mullericpicus pulverulentus. A total of 30 species characteristic of the Indo-Malyan tropical dry zone has been recorded, representing a high percentage of 68 per cent of the total recorded in Nepal in this biome. Further research of species diversity focusing on birds and mammals in DDWR and the preparation and implementation of a conservation management strategy including increasing the conservation awareness outreach activities amongst local communities are recommended.